Islam dan Politik Identitas: Konflik pada Gerakan 212 dalam Perspektif Sejarah Indonesia - Adam, Yusril Fahmi (NALAR, 2022)
Politics of identity often triggers conflicts to emerge on the surface of Indonesian society. In this case, the 212 movement is a formal object that is considered to be included in politics of identity that uses Islam as the spirit of its movement. This article aims to analyze the politics of identity of the 212 movements through a historical frame. This study uses historical methods, as well as sociological approaches and conflict theory as tools in analyzing historical events. With the methods, approaches, and theories used, this research will then not only work in a narrative descriptive but rather in an analytical descriptive, so that this article can produce an authoritative work on social history in the contemporary era. The result of this study is that the 212 movements began when there was blasphemy committed by Basuki Tjahaja Purnama (Ahok) during a speech in the Kepulauan Seribu. In its development, the 212 movements changed their orientation to a politics of identity movement which often caused conflicts during religious and socio-political life. During various conflicts that have arisen, the government together with moderate Islamic organizations such as NU and Muhammadiyah must be role models to maintain the unity of the Indonesian nation.Keywords: 212 Movement; Islamic Ideology; Politics of Identity